Customary Authority and Islamic Family Law Governance under Legal Pluralism: Toward a Limited Integration Model in the Sultanate of Ternate, Indonesia - Samad Umarama; Syaifuddin; Mahmudah; Jonatan Lassa; Abu Sanmas; Rusmiyanti Wontami (Legitima : Jurnal Hukum Keluarga Islam, 2026)
Purpose – This study aims to analyze the customary authority of the Sultanate of Ternate in the governance of Islamic family law in Indonesia within the framework of legal pluralism. This study is based on the fact that disputes within Muslim families are not always resolved through the religious courts but through community-based social mechanisms, such as customary mediation, family consultations, and the roles of customary and religious leaders. Methods – This study employs a socio-legal approach with a qualitative research design. Data were obtained through in-depth interviews with traditional leaders, religious figures, and members of the community, as well as through an analysis of relevant academic literature. The analysis was conducted using thematic analysis, integrating empirical findings with the theory of legal pluralism. Findings – The research findings indicate that customary authorities in the Sultanate of Ternate function as informal actors in the administration of Islamic family law through three main roles: establishing socio-cultural legitimacy, facilitating pre-litigation mediation, and providing customary consultation in family disputes. However, these roles do not supersede the authority of the Religious Courts but rather complement dispute resolution mechanisms through social reconciliation and the strengthening of legal processes. Further findings of this study indicate that legal pluralism carries risks of legal uncertainty, gender bias, forum shopping, and the politicization of customary practices if not accompanied by clear boundaries on authority. This study proposes a Model of Limited Integration of Customary Authority, namely a model that positions the Sultanate’s authority as a non-litigious consultative and mediatory institution while maintaining the constitutional authority of the Religious Courts to adjudicate cases. This model is built upon five key principles: accountability, documentation, voluntariness, gender protection, and child protection. Research implications – Theoretically, this study contributes to the integration of the theories of legal pluralism, the semi-autonomous social field, and ‘justice in many rooms’ in explaining the relationship between customary legitimacy and the national legal system in the context of Islamic family law.